Evaluation of Lateral and Axial Deformation for Earth Pressure Balance (EPB) Tunnel Construction Using 3 Dimension Finite Element Method - Fahmi Aldiamar; Masyhur Irsyam; Bigman Hutapea; Endra Susila; Ramli Nazir (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Mass Rapid Transit Jakarta (MRTJ) phase 1 tunnel construction using the earth pressure balance method has been completed and surface settlement and lateral displacement data according to elevation and inclinometer readings has been collected to evaluate the effect of tunnel’s construction on surrounding infrastructure. Soil stratification along the research area, defined according to boring logs and soil parameters for the hardening soil model (HSM) and the soft soil model (SSM), was determined by optimization of stress-strain curve fitting between CU triaxial test, consolidation test and soil test models in the Plaxis 3D software. Evaluation of the result of surface settlement measurements using an automatic digital level combined with geodetic GPS for elevation and position control points showed that the displacement behavior was affected by vehicle load and stiffness of the pavement. Lateral displacement measurements using inclinometers give a more accurate result since they are placed on the soil and external influences are smaller than surface settlement measurement. The result of 3D finite element modeling showed that surface settlement and lateral displacement during TBM construction can be predicted using HSM with 2% contraction. SSM and the closed-form solutions of Loganathan and Poulos are unable to provide a good result compared to the actual displacement from measurements.